Quality assurance in the Portuguese census: the contribution of the balanced scorecard - Rosa, A.; Reis, E.; Vicente, P. (The Quality Management Journal, 2016)
This article describes how the balanced scorecard methodology and associated procedures were developed and implemented as the framework for the quality assurance strategy of the fieldwork in the 2011 Portuguese Population and Housing Census. The main goal of a census operation is to provide high-quality statistical information on population, buildings, and dwellings that meet users’ needs. The most critical activity of a census is the fieldwork operation where the distribution, completion, and recollection of census questionnaires are handled. Due to the dimension, complexity, and need to guarantee the final product quality of the census 2011 operation, the balanced scorecard methodology was elected as the framework for the quality assurance strategy implementation. This was the first time such a management system was used in a census operation. In terms of academic research on census quality control, the quality focus has been on the net undercount based on post enumeration survey. On the contrary, the authors’ concern is about how to ensure quality enumeration work during the census operation. The balanced scorecard methodology allowed integrating the operational execution of goals and its control into a single census management tableaux du bord, which allowed the provision of updated information on the ongoing processes and, thus, the ability to make timely corrections for those targets that suffered deviations.